2008
DOI: 10.1016/j.foodchem.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and antioxidant activities of oligomeric and polymeric procyanidin fractions from grape seeds

Abstract: Two procyanidin fractions, namely oligomers and polymers isolated from grape seed methanolic extract were characterized. Phenolic composition and procyanidin purity of these fractions were determined by normal-phase and reverse-phase HPLC, thioacidolysis-HPLC, ESI-MS analyses, formaldehyde-HCl precipitation and elemental analysis. Antioxidant activities of these fractions and other well-known antioxidants were measured using xanthine-xanthine oxidase system for generating superoxide radical ({O2(-)}), the DPPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
155
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 29 publications
(43 reference statements)
19
155
2
1
Order By: Relevance
“…In our study WFB, that had the highest content of proanthocyanidins, showed a similar radical scavenging activity to the extracts (AEB and EEB) with higher phenols and flavonoids content than WFB. Proanthocyanidins certainly contributed to the free radical scavenging activity of the extracts, as demonstrated by others (Kimura et al, 2008;Spranger et al, 2008). The extracts presented Fe 3+ reducing capacity similar to ascorbic acid and higher than BHT and it was also concentrationdependent.…”
Section: Resultssupporting
confidence: 56%
“…In our study WFB, that had the highest content of proanthocyanidins, showed a similar radical scavenging activity to the extracts (AEB and EEB) with higher phenols and flavonoids content than WFB. Proanthocyanidins certainly contributed to the free radical scavenging activity of the extracts, as demonstrated by others (Kimura et al, 2008;Spranger et al, 2008). The extracts presented Fe 3+ reducing capacity similar to ascorbic acid and higher than BHT and it was also concentrationdependent.…”
Section: Resultssupporting
confidence: 56%
“…The monomers presented higher antioxidant capacity than dimers (procyanidins B2 and B) and trimers (procyanidin C). It is not in agreement with data found in literature that showed that the antioxidant capacity of grape seed procyanidins was related to their degree of polymerization, for instance, the monomers were the compounds with less antioxidant power (Spranger et al 2008). However, to the best of our knowledge, there is no data that shows this statement in cocoa procyanidins.…”
Section: Individual Antioxidant Capacity Of Phenolic Compoundscontrasting
confidence: 96%
“…Additionally, GSPE contains mainly flavonoids, all involved in ameliorating the oxidative stress in vitro and in vivo by increasing the endogenous antioxidant status (Martinez-Florez et al 2002). Besides, GSPE can clear off free radicals and protect the overoxidative damage caused by free radicals (Spranger et al 2008). Furthermore, the observed protective action of GSPE on the antioxidants may be due to the protection of SH groups in GSH from oxidative damages via free radical quenching action of the di-OH (catechol) structure in the B ring of GSPE (Ishige et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Such products may increase lipid peroxidation, which can be harmful to different organs including liver and kidney (Soliman et al 2010). On the other hand, these free radicals, known to cause oxidative stress, can be prevented or reduced by dietary natural antioxidants through their capacity to scavenge these products (Spranger et al 2008;Wang et al 2008). The present study was undertaken to determine whether GSPE can prevent and/or reduce GA3-induced oxidative stress by examining different biochemical parameters of oxidative damage in the liver and kidney of male rats.…”
Section: Discussionmentioning
confidence: 99%